2013
DOI: 10.1007/s00018-013-1446-6
|View full text |Cite
|
Sign up to set email alerts
|

A creature with a hundred waggly tails: intrinsically disordered proteins in the ribosome

Abstract: Intrinsic disorder (i.e., lack of a unique 3-D structure) is a common phenomenon, and many biologically active proteins are disordered as a whole, or contain long disordered regions. These intrinsically disordered proteins/regions constitute a significant part of all proteomes, and their functional repertoire is complementary to functions of ordered proteins. In fact, intrinsic disorder represents an important driving force for many specific functions. An illustrative example of such disorder-centric functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 137 publications
(186 reference statements)
5
116
0
Order By: Relevance
“…In the process, the unstructured loop of L4 possibly transitions to a folded state similar to what is found in the structures of mature 60S subunits (Ben-Shem et al 2011). Our results support prevailing models that depict coupled binding and folding of r-protein extensions with rRNA during ribosome biogenesis (Klein et al 2004;Timsit et al 2009;Peng et al 2014). Moreover, consistent with the late pre-rRNA processing defect observed when the internal loop of L4 is removed, recent studies demonstrate that the functionally important centers of ribosomal subunits are assembled during later stages in assembly (Bussiere et al 2012;Strunk et al 2012;Karbstein 2013;Gamalinda et al 2014;Garcia-Gomez et al 2014).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In the process, the unstructured loop of L4 possibly transitions to a folded state similar to what is found in the structures of mature 60S subunits (Ben-Shem et al 2011). Our results support prevailing models that depict coupled binding and folding of r-protein extensions with rRNA during ribosome biogenesis (Klein et al 2004;Timsit et al 2009;Peng et al 2014). Moreover, consistent with the late pre-rRNA processing defect observed when the internal loop of L4 is removed, recent studies demonstrate that the functionally important centers of ribosomal subunits are assembled during later stages in assembly (Bussiere et al 2012;Strunk et al 2012;Karbstein 2013;Gamalinda et al 2014;Garcia-Gomez et al 2014).…”
Section: Resultssupporting
confidence: 85%
“…Recent atomic structures of eukaryotic ribosomes showed that in contrast to the conserved internal r-protein extensions that penetrate the core, eukaryote-specific tails mainly thread across the surface of the ribosome (Ben-Shem et al 2011). These internal loops and external tails of r-proteins are intrinsically disordered; hence, the current model is that r-protein extensions chaperone co-folding of rRNA and/or stabilize tertiary interactions during assembly (Wilson and Nierhaus 2005;Timsit et al 2009;Peng et al 2014). However, the overarching function of r-protein extensions in the eukaryotic ribosome, especially regions not present in bacteria, remains to be established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we had to exclude viruses that were not considered in Ref. [47] and archaea that had small sample size.Similarly as in [48,49], we quantified the sequence conservation using relative entropy [50], which was computed from the Weighted Observed Percentages (WOP) profiles produced by PSI-BLAST [51]. PSI-BLAST was run with default parameters (−j 3, −h 0.001) against the nr database.…”
mentioning
confidence: 99%
“…Such extended domains are enriched in RNA interacting proteins, suggesting roles in the assembly, structure, and function of many different RNPs (Cumberworth et al 2013;Van Der Lee et al 2014). For example, 38 of the 78 r-proteins in yeast contain such extensions (Peng et al 2014). In the ribosome, disordered regions of r-proteins have been suggested to function as stabilizers of the tertiary structure of rRNA, as RNA chaperones to avoid kinetic traps, and as binding sites of dedicated assembly chaperones (Tompa 2003;Tompa and Csermely 2004;Van Der Lee et al 2014).…”
Section: Introductionmentioning
confidence: 99%